การพัฒนารูปแบบการบริหารที่เหมาะสมสำหรับสถาบันการอาชีวศึกษา - ขวัญชัย พานิชการ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The proposes of this research are for educating the obligation and state of vocational education institutions, management model of institution with the educational obligation similar to vocational education institutions and also development of an appropriate management model for vocational education institutions. For educating the obligation and state of vocational education institutions, the researcher used the questionnaire to survey the school executives belong to Office of the Vocational Education Commission, the Office of the Vocational Education Commission executives, The Vocational Education Commissions and Professional Qualifications Commissions, 257 people. In the part of educating management model of institution with the educational obligation similar to vocational education institutions, used the questionnaire to survey eight University executives. After that, educating appropriate management model for vocational education institutions that will be found by using the information which was already analyzed and synthesized to draft the appropriate management model. Then, the model was reviewed and evaluated about appropriation and possibility by an expert and person who concerned with vocational education institutions. Next, all of the comments will be brought to improve the management model for vocational education institutions to be appropriate. Finally, there was making up the focus group to consider the management model for vocational education institutions. The result of this research is that the vocational education institutions which will be found should be both of specific institution and completed institution. Therefore, it should be located in any provinces and also be opened the department which matches with the requirements in that areas and have six obligations; 1) management education of vocational education at vocational certificate, vocational diploma and bachelor s degree, 2) Academic service for social of vocational education, 3) Research for creating the new knowledge for using in daily life of vocational education, 4) Research for creating knowledge and innovation of vocational education, 5) Preservation of Local Wisdom and 6) Preservation of Art And Culture. Moreover, the management model should be participation model and has the management structure that decentralizes to other faculties, colleges and units. The management should be in the way of official institution. Furthermore, the important styles of participated management model should be that 1) Set up the level of the propose by institution or unit, 2) Process of setting up the propose should come from the agreement of the colleagues, 3) the relationship between propose and decision should refer to the agreed propose or institution propose, 4) the nature of decision process should make reasonably, 5) the nature of structure should be horizon structure (there are the hierarchy.), 6) the affect of environment that connects to the popularity should depend on participated decision, 7) the lead should pay attention to the participated decision and 8) the leader model should make the change by taking all participation and also making relationship.